2000
DOI: 10.1021/la000159p
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Surface Heterogeneity of a Polymer Blend:  An Adhesion-Force-Distribution Study Using the Atomic Force Microscope

Abstract: Adhesion force mapping using atomic force microscopy has been used to investigate a phase-separated blend of poly(methyl methacrylate) (PMMA) and poly(dodecyl methacrylate) (PDDMA). Comparison of the results from the blend with those from the pure constituent polymers showed that force mapping could identify PMMA- and PDDMA-rich areas in the blend. The adhesion maps produced were deconvoluted from sample topography and contrasted with data obtained from contact angle goniometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…Examples are the identification of patterns in polystyrene generated by oxygen plasma treatment [1169], wear removal of a perfluoropolyether lubricant from silicon surfaces [683], phase separation in polymer blends [1170], characterization of the hydrophilicity of TiO 2 :OH films before and after UV treatment [1171], the structure of collagen adsorbed on polystyrene [1172], hole formation by aging in Langmuir-Blodgett monolayer films of stearic acid [1173,1174], heat induced changes of ovalbumin (white egg protein) layers on mica in aqueous solution [1175]. Reynaud et al [298] used single force curves on bulk samples reference materials for calibration and then measured in force volume mode the Young's modulus of a biphasic PMMA/polyacrylate polymer system.…”
Section: Force Volume Modementioning
confidence: 99%
“…Examples are the identification of patterns in polystyrene generated by oxygen plasma treatment [1169], wear removal of a perfluoropolyether lubricant from silicon surfaces [683], phase separation in polymer blends [1170], characterization of the hydrophilicity of TiO 2 :OH films before and after UV treatment [1171], the structure of collagen adsorbed on polystyrene [1172], hole formation by aging in Langmuir-Blodgett monolayer films of stearic acid [1173,1174], heat induced changes of ovalbumin (white egg protein) layers on mica in aqueous solution [1175]. Reynaud et al [298] used single force curves on bulk samples reference materials for calibration and then measured in force volume mode the Young's modulus of a biphasic PMMA/polyacrylate polymer system.…”
Section: Force Volume Modementioning
confidence: 99%
“…[33] In preliminary studies, work of adhesion, as determined from force±distance curves, has been correlated with independently determined surface free energies. [34] However, considerable advances in our appreciation of the factors that influence the observed AFM force±distance curves is needed before the technique can be routinely applied to the determination of surface energies; in particular, the effects of surface heterogeneities resulting from molecular organization phenomena at the outermost atomic layers of the film structures, [35] and the implications associated with surface-roughness-induced phenomena, as related to the increased area of the contact between the probing tip and the sample, [36] need to be considered in detail. …”
Section: Atomic Force Microscopy (Afm) Force Measurements and Mappingmentioning
confidence: 99%
“…Eaton et al investigated the capability of the adhesive force measurement technique to discriminate between different domains of polymer blends based on their surface energetic and nanoscale stiffness [145]. The adhesive force measurement results on PDDMA/PMMA thin films demonstrated that the average force of adhesion was much higher for PDDMA-rich domain compared to PMMA regions, mainly due to its higher surface deformation and, consequently, greater tip-sample real contact area [146,147]. Begat et al glued pharmaceutical micro-particles from various inhaler formulations to a tipless cantilever and measured the adhesive forces between them and a reference substrate with well-defined surface texture [148].…”
Section: Nanoscale Adhesion On Viscoelastic Surfacesmentioning
confidence: 99%